2004
DOI: 10.1590/s0100-39842004000300004
|View full text |Cite
|
Sign up to set email alerts
|

Achados ultra-sonográficos abdominais em pacientes com dengue

Abstract: OBJETIVO: Apresentar os achados ultra-sonográficos abdominais em pacientes com dengue e compará-los aos descritos na literatura. MATERIAIS E MÉTODOS: Foram realizados exames ultra-sonográficos abdominais de 38 pacientes, 25 do sexo feminino e 13 do sexo masculino, com idade média de 35 anos, com diagnóstico de dengue sorologicamente confirmado. Os achados foram comparados com os descritos na literatura. RESULTADOS: Os achados ultra-sonográficos mais relevantes foram espessamento difuso da parede da vesícula bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…do Vabo et al (2004) found among 38 patients submitted to abdominal ultrasound diffuse gallbladder wall thickening (47%), abdominal and/or pelvic free fluid in (31%), splenomegaly (29%), hepatomegaly (26%) and perivesicular fluid (26%). Khan et al (2008) detected ascites on abdominal ultrasound in two patients who fulfilled all the criteria for DHF.…”
Section: Discussionmentioning
confidence: 90%
“…do Vabo et al (2004) found among 38 patients submitted to abdominal ultrasound diffuse gallbladder wall thickening (47%), abdominal and/or pelvic free fluid in (31%), splenomegaly (29%), hepatomegaly (26%) and perivesicular fluid (26%). Khan et al (2008) detected ascites on abdominal ultrasound in two patients who fulfilled all the criteria for DHF.…”
Section: Discussionmentioning
confidence: 90%
“…Fasting has shown to be advantageous only in the evaluation of the gallbladder by the sonographer 2 ( p = 0.032), this advantage being not observed by the sonographer 1. phy in cases of abdominal emergency (15,16) . Such phenomenon contributes for an extension of the waiting time for the previously scheduled inpatients, considering that, usually, patients coming from the emergency department are examined at the intervals between previously scheduled studies.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonography is a safe, low-cost imaging method that do not utilizes ionizing radiation, with high sensitivity to detect early signs of plasma leakage, many times in anticipation of the most critical period of the disease corresponding to the fever abatement to a temperature < 38°C, that is known as defervescence, where the risk for shock is higher. This critical phase extends from the third to the fifth day of febrile disease in children, where gallbladder wall thickening and cavitary effusion are ob-served in addition to severe abdominal pain, persistent emesis and increased hematocrit levels (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) .…”
Section: Main Sonographic Findingsmentioning
confidence: 99%
“…Dengue fever is an arbovirosis responsible for annual epidemics in Brazil. It is caused by one of the four serotypes of dengue virus (DEN1, DEN2, DEN3 and DEN4), with a clinical spectrum ranging from asymptomatic to severe, life-threatening conditions (1)(2)(3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation